Perancangan Sign System Dan Way Finding Di Stadion Si Jalak Harupat Kabupaten Bandung - Sophia Purbasari; Mohamad Syaban Shodiqin (Universitas Informatika dan Bisnis Indonesia, 2020)
Si Jalak Harupat Stadium is one of the international stadium in Bandung and as homebase of football club Persib Bandung. The stadium has media information such as sign systems and wayfindings that are not effective and not really helping in ensuring order and safety of supporters when watching the game in stadium. Many supporters are difficult to find the location of the facilities in the stadium. Furthermore, supporters are also not well ordered when queuing up tickets or occupy a seat that does not match with the seat number on teh tiket. Therefore, it is necessary to design a dear and informative sign systems and wayfindings that can make supporters more well ordered and ensure their savety when theyre in the stadium. The design of sign systems and wayfinding are using a strategy message with artistic and communication approach. The creative strategy with visual approach is using symbol form in accordance with Si Jalak Harupat Stadium, the selection of fonts and colors on the sign system and wayfinding design adjusted and adapted from the colors that already used in the stadium building. For supporting media of sign system and wayfinding design, there is a direction map plan that designed as anaddition information media that can help the supporter to find the direction more dearly. These sign systems and wayfinding design are expected to provide solutions in creating order and safety supporter in Si Jalak Harupat Stadium that accordance with FIFA the international football stadium rules.